2014
DOI: 10.1021/jp412031f
|View full text |Cite
|
Sign up to set email alerts
|

Time-Domain Study of the S3 State of 9-Fluorenone

Abstract: We report a combined gas phase and solution phase study of 9-fluorenone. The structure and dynamics of isolated fluorenone in the S3-state were studied by resonant enhanced multiphoton ionization with picosecond pulses in a free jet of molecules excited between 285 and 312 nm. Ionization was performed with a second ps-pulse at 351 nm. The electronic spectrum is structured, and the origin of the C (1)B2 ← X (1)A1 transition was observed at 32,122 cm(-1). Several vibrational fundamentals appear in the spectrum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…As noted above, it has long been suggested that an increased possibility for ISC in nonpolar solvents is the reason for the decreased fluorescence of 9‐FL in nonpolar solvents compared with polar solvents . Recent experiments suggest ISC to a triplet state following red‐edge excitation of 9‐FL in cyclohexane, which also supports the claim of ISC . The similar responses of BFb and 9‐FL in cyclohexane suggest that ISC may also explain the low fluorescence quantum yield and short fluorescence lifetime results for BFb as well.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As noted above, it has long been suggested that an increased possibility for ISC in nonpolar solvents is the reason for the decreased fluorescence of 9‐FL in nonpolar solvents compared with polar solvents . Recent experiments suggest ISC to a triplet state following red‐edge excitation of 9‐FL in cyclohexane, which also supports the claim of ISC . The similar responses of BFb and 9‐FL in cyclohexane suggest that ISC may also explain the low fluorescence quantum yield and short fluorescence lifetime results for BFb as well.…”
Section: Resultsmentioning
confidence: 99%
“…In polar solvents, the energy difference between the ground and first excited triplet is similar, while the difference between the ground and second excited triplet increases to approximately 1.1 eV . For several solvents, experimental triplet‐triplet absorption peaks have been observed in the region between 550 and 700 nm (~1.8‐2.3 eV) [2d, 15, 21, 23]. Interestingly, the experimental absorption energies reported in these studies all roughly match the energies differences between the excited n‐π* triplet state and the ground π‐π* triplet state predicted in the present calculations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…25,26 However, although multiphoton absorption 27,28 in uorenone derivatives has been reported many times, systematic investigations into excited-state associated nonlinear absorption are rare. [29][30][31] Furthermore, most of the research focuses on nonlinear absorption (NLA), little attention has been paid to the ultrafast nonlinear refraction (NLR) in uorenone derivatives.…”
Section: Introductionmentioning
confidence: 99%